2018
DOI: 10.1111/jace.16172
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and piezoelectricity of BaZrO3‐modified (K,Na)NbO3 lead‐free piezoelectric thin films

Abstract: K,Na)NbO 3 (KNN) is a promising lead-free ferroelectric/piezoelectric system, to which incorporating BaZrO 3 can greatly enhance its piezoelectricity, but the mechanism is not clear. This work was conducted to investigate the phase transition in the BaZrO 3 -modifed KNN system and its contribution to piezoelectricity enhancement, using thin films with a fixed orientation and high compositional homogeneity fabricated by a sol-gel method. Two ferroelectric-to-ferroelectric phase transitions are revealed, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…Due to low cost and the ubiquity of Si in electronics, platinized silicon (SiPt, Pt/TiO2/SiO2/Si) is by far the most used substrate in ferroelectric oxide thin film CSD synthesis 17 . KNN thin film synthesis is no exception, and the majority of studies of KNN thin films are based on using SiPt substrates [19][20][21][22][23][24][28][29][30][31][32][33][34][35][36][40][41][42][43][46][47][48]52,53 , while a few other studies are reported using other substrates like SiO2/Si 38,58,59 , ZrO2/Si 44,45 , LaNiO3/Si 57 , Pt/MgO 39 , Pt/Al2O3 49,58 , metals 50,51,54 and SrTiO3 (STO) 18,[25][26][27]37,55,56 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to low cost and the ubiquity of Si in electronics, platinized silicon (SiPt, Pt/TiO2/SiO2/Si) is by far the most used substrate in ferroelectric oxide thin film CSD synthesis 17 . KNN thin film synthesis is no exception, and the majority of studies of KNN thin films are based on using SiPt substrates [19][20][21][22][23][24][28][29][30][31][32][33][34][35][36][40][41][42][43][46][47][48]52,53 , while a few other studies are reported using other substrates like SiO2/Si 38,58,59 , ZrO2/Si 44,45 , LaNiO3/Si 57 , Pt/MgO 39 , Pt/Al2O3 49,58 , metals 50,51,54 and SrTiO3 (STO) 18,[25][26][27]37,55,56 .…”
Section: Introductionmentioning
confidence: 99%
“…Sampel yang mempunyai ukuran kristal yang besar memiliki nilai FWHM yang kecil. Hasil penelian ini juga dilaporkan oleh Luo et al (2019) Tabel 1 menunjukkan ukuran kristal berbanding terbalik dengan nilai FWHM dimana laju kenaikan suhu yang kecil menyebabkan ukuran kristal membesar. Pada sudut 2θ = 22.78° nilai FWHM untuk 5°C/min sebesar 0,360° dan nilai ukuran kristal sebesar 3,94 nm, sedangkan untuk 10°C/min nilai FWHM sebesar 0,360° dan ukuran kristal 3,22 nm.…”
Section: Hasil Penelitianunclassified
“…With the promulgation and enforcement of relevant regulations, the usage of lead-based material is limited and the exploration on the environment friendly material is strengthened [5][6][7]. Among them, (K,Na)NbO 3 (KNN) is favored by researcher for the high Curie temperature (T C ) and excellent piezoelectric response of its ceramic form [8][9][10][11][12][13][14]. Unfortunately, due to the polymorphic phase transition (PPT) effect of the structural inhomogeneity, the electrical properties of KNN are sensitive to temperature.…”
Section: Introductionmentioning
confidence: 99%